Juridical Review of Consensual Principle in the Scope Legal Agreement - Nurfaidah (MultiTech Publisher, 2023)
Legal interests that want order and uphold justice in society, put the consensual principle as a demand for legal certainty. As we understand that humans who live in an orderly society must be able to obey their words or utterances because it is something that is absolute from a good legal system. So that the law of the agreement has been declared valid if it has reached an agreement. The consensual principle is contained in article 1320 of the Civil Code which of course supports and complements each other with article 1338 paragraph 1 of the Civil Code. Meanwhile, in terms of buying and selling, it is contained in article 1458 of the Civil Code. The legal requirements for an agreement in Article 1320 of the Civil Code can be divided into 2 requirements, namely subjective conditions consisting of elements of agreement and skill and objective conditions consisting of elements of a certain matter and a legal cause.